The Role of AI in Driving Human Resource Management to Improve Employee Competence and Intrinsic Motivation - Ali Zaenal Abidin; Ade Hilman Maulana; Jakoep Ezra Harianto; Syech Idrus (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The rapid development of artificial intelligence has transformed the way organizations manage their workforce, particularly in the areas of recruitment, performance evaluation, and employee development. While many applications have focused on increasing operational efficiency, less attention has been given to how artificial intelligence can contribute to competence development and foster intrinsic motivation among employees. This article aims to provide a comprehensive review of the role of artificial intelligence in human resource management, with a specific focus on how it can be used to support personalized learning pathways and motivational strategies. The study applies a qualitative literature review method, synthesizing recent research and practical cases where artificial intelligence has been implemented in workforce management. Findings reveal that artificial intelligence is capable of creating adaptive learning environments, delivering real-time and personalized feedback, and aligning tasks with individual strengths and career aspirations. These functions not only improve the efficiency of employee training but also enhance engagement, satisfaction, and long-term growth. The conclusion highlights that artificial intelligence offers great potential to strengthen both competence development and intrinsic motivation when applied thoughtfully. However, successful implementation requires balancing technological innovation with human-centered approaches to ensure fairness, trust, and sustainable employee development.